Atezolizumab-Induced Bell's Palsy in a Patient With Small Cell Lung Cancer - Asim Kichloo MD; Michael Stanley Albosta MD; Shakeel M. Jamal MD; Michael Aljadah MD; Farah Wani MD; Insija Selene MD; Jagmeet Singh MD; Asma Taj MD (SAGE Publishing, 2020)
Immune checkpoint inhibitors are rapidly becoming popular therapeutic options for patients suffering from a number of malignancies. Atezolizumab is a programmed cell death ligand-1 inhibitor, and binding to this ligand decreases the ability of tumor cells to evade the immune system, resulting in self-tolerance. While inhibition of these molecules leads to increased T-cell destruction of tumor cells, it also may lead to autoimmune destruction of healthy cells. Neurotoxicity is a rare complication of immune checkpoint inhibitor therapy, and facial palsy as a complication of atezolizumab therapy has only been reported in one additional study. We present the case of a 68-year-old female with a history of small cell carcinoma of the lung presenting with sudden-onset facial palsy and numbness of the distal extremities in the setting of receiving atezolizumab immunotherapy. Our patient was managed with temporary cessation of her immunotherapy, oral prednisone, and supportive measures. Within 4 weeks, the patient had complete resolution of her facial palsy and was able to resume immunotherapy without further complication. Clinicians should be aware of this rare adverse effect in order to enact early management including temporary cessation of therapy to prevent morbidity in patients undergoing immunotherapy.